An Intensive Combination of Bobath Therapy and Core Stability Exercises Is More Effective In Improving the Sitting Balance of Cerebral Palsy Children - Anwar, Suharto; Suriani, Suriani; Gasma, Asmawati (International Journal of Multidisciplinary Approach Research and Science, 2023)
This research is an experimental study with a pretest – post one group design which aims to analyze the effectiveness of intensive bobath therapy and core stability exercises on sitting balance in children with Cerebral Palsy. A total of 17 Cerebral Palsy children were given bobath therapy and core stability exercises for 10 weeks, with a dose: 1 time/day, 4 times a week with a treatment time of 60 minutes for each child. The research subjects were children suffering from Cerebral Palsy with the age criteria of 1 year sitting unbalanced. Carried out from February to July 2023. Sitting balance is measured using a sitting flat scale. The research subjects consisted of 13 men (76.47%) and 4 women (23.53%) with GMFCS categories III and IV. Average age of research subjects: 36.5758 ± 15.02504. The results of the statistical test using Wilcoxon obtained a p value = 0.001. Conclusion: Bobath therapy and core stability exercises are more effective in increasing sitting level scale scores in Cerebral Palsy children.